Intracardiac Teratoma in a Child: A Rare Site of a Common Tumor. Issue 5 (July 2021) - Nakra, Tripti; Chandrashekhara, S.H.; Rajashekar, Palleti; Ray, Ruma; Arava, Sudheer
Abstract : Primary intracardiac teratoma is a rare cardiac tumor with few cases reports in neonates and children. The authors present a case of an 8-year-old boy diagnosed with a cystic mass within the heart. The mass lesion was originating from the interventricular septum and was obliterating the ventricular chambers. Clinically, the mass was suspected to be a hydatid cyst. Surgical excision of the cyst was done that was confirmed histopathologically as mature teratoma. Although rare, it should be considered in the differential diagnosis of cystic lesions of heart when evaluating mass lesions in the pediatric age group.